The study of the production of heavy flavour muons as a function of charged-particle multiplicity in proton-proton collisions at 8TeV with ALICE at the LHC - Mhlanga, Sibaliso (Department of Physics, 2016)
ALICE (A Large Ion Collider Experiment) is a detector designed and optimized to study ultra relativistic heavy-ion collisions in which a hot, dense and strongly interacting Quantum Chromodynamics (QCD) medium called the Quark Gluon Plasma (QGP) is created. ALICE also studies proton-proton collisions both to test for pertubative QCD (pQCD) theories and as reference for comparison with heavy-ion collisions. ALICE measures hadrons, leptons, and photons up to very high transverse momentum (pT), up to ∼100 GeV/c. It consists of a central barrel which covers a rapidity of | η | < 0.9 and a Muon Spectrometer which covers the forward rapidity, -4 < η < -2.5. The Muon Spectrometer measures dimuons from the decay of quarkonia (charm-anti-charm (c c ) e.g. J/Ψ), as well as single muons from heavy flavours (e.g. charm (c) and bottom (b) hadrons) and electroweak bosons (W ± , Z 0 ), which are tools for studying QGP as well as the initial conditions of the collision. In this thesis the production of heavy flavours is measured via the contribution of their muonic decays to the inclusive pT -differential muon yield, reconstructed with the Muon Spectrometer and studied as a function of charged-particle multiplicity in proton-proton collisions at 8 TeV centre-of-mass energy. The charged-particle multi- plicity is measured in the central barrel. The aim of the study is to investigate the role of multi-parton interactions in the production of heavy quarks, particularly heavy flavour.